Extracorporeal Membrane Oxygenation as a Bridge for Heart Failure and Cardiogenic Shock - Zhong, Zhao-peng (Biomed Res Int, 2016)
Heart failure (HF) can be defined as cardiac structural or functional abnormality leading to a series of symptoms due to deficiency of oxygen delivery. In the clinical practice, acute heart failure (AHF) is usually performed as cardiogenic shock (CS), pulmonary edema, and single or double ventricle congestive heart failure. CS refers to depressed or insufficient cardiac output (CO) attributable to myocardial infarction, fulminant myocarditis, acute circulatory failure attributable to intractable arrhythmias or the exacerbation of chronic heart failure, postcardiotomy low CO syndrome, and so forth. Epidemiological studies have shown that CS has higher in-hospital mortality in patients with AHF. Besides, we call the induced, sustained circulatory failure even after administration of high doses of inotropes and vasopressors refractory cardiogenic shock. In handling these cases, mechanical circulatory support devices are usually needed. In this review, we discuss the current application status and clinical points in utilizing extracorporeal membrane oxygenation (ECMO).